Pemaknaan School Well-being pada Siswa SMP: Indigenous Research - Rudy Yuniawati; Nissa Tarnoto (Jurnal Psikologi Islam dan Budaya, 2019)
This study examined school well-being from the perspective of junior high school students and influential factors of school well-being in the context and culture of Indonesia. This study used qualitative method with indigenous approach. This study was conducted in two phases, the first stage research subjects were 223 students and the second stage were 68 students. The finding shows that school well-being includes student satisfaction with learning programs in schools, have good relationships with other students and teachers, feeling happy doing worship activities and deepening religious knowledge which is a characteristic of religious-based schools. However, the learning schedule is not satisfactory because many empty hours made students feel bored, the class situation was not conducive, and some subject matters were not complete. The factors that influence school well-being in students are internal motivation to study, positive relationships with peers and teachers, and religiosity.